2021
DOI: 10.3390/brainsci11101306
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory and Lifestyle-Based Brain Health Program for Subjective Cognitive Decline: Self-Implementation versus Coaching

Abstract: Although recent studies have explored the potential of multidomain brain health programs, there is a dearth of literature on operationalizing this research to create a clinical treatment program specifically for subjective cognitive decline (SCD). Patients seen by geriatricians in primary care and by behavioral neurology services at our institution presenting with SCD were recruited via a patient-appropriate flyer. After all participants had a 1-h brain health consultation with a neuropsychologist and were pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…A recent systematic review of randomized control trials (RCTs) for interventions at the stage of SCD found that, overall, education programs, compared to cognitive training, physical training, or mind–body interventions, were most effective in improving memory function 133 . Several of these interventions, designed to support socialization and brain health education, appeared to support quality of life and holistic functioning in individuals with SCD 134,135 . Multimodal educational and health programs, involving combinations of brain health education, mindfulness practice, music listening, and/or exercise, were generally associated with increased subjective cognitive functioning post‐intervention or reductions in anxiety levels 136,137 .…”
Section: Interventions In Scdmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review of randomized control trials (RCTs) for interventions at the stage of SCD found that, overall, education programs, compared to cognitive training, physical training, or mind–body interventions, were most effective in improving memory function 133 . Several of these interventions, designed to support socialization and brain health education, appeared to support quality of life and holistic functioning in individuals with SCD 134,135 . Multimodal educational and health programs, involving combinations of brain health education, mindfulness practice, music listening, and/or exercise, were generally associated with increased subjective cognitive functioning post‐intervention or reductions in anxiety levels 136,137 .…”
Section: Interventions In Scdmentioning
confidence: 99%
“… 133 Several of these interventions, designed to support socialization and brain health education, appeared to support quality of life and holistic functioning in individuals with SCD. 134 , 135 Multimodal educational and health programs, involving combinations of brain health education, mindfulness practice, music listening, and/or exercise, were generally associated with increased subjective cognitive functioning post‐intervention or reductions in anxiety levels. 136 , 137 Another recent systematic review also found strong evidence for cognitive/mental/physical training on cognitive and non‐cognitive outcomes in SCD individuals.…”
Section: Interventions In Scdmentioning
confidence: 99%